Diazotrophy modulates cyanobacteria stoichiometry through functional traits that determine bloom magnitude and toxin production. Issue 2 (24th November 2022) - Wagner, Nicole D.; Osburn, Felicia S.; Taylor, Raegyn B.; Back, Jeffrey A.; Chambliss, C. Kevin; Brooks, Bryan W.; Scott, J. Thad
Abstract: Harmful cyanobacterial blooms are an increasing threat to water quality. The interactions between two ecophysiological functional traits of cyanobacteria, diazotrophy (nitrogen [N]‐fixation) and N‐rich cyanotoxin synthesis, have never been examined in a stoichiometric explicit manner. We explored how a gradient of resource N : phosphorus (P) affects the biomass, N, P stoichiometry, light‐harvesting pigments, and cylindrospermopsin production in a N‐fixing cyanobacterium, Aphanizomenon . Low N : P Aphanizomenon cultures produced the same biomass as populations grown in high N : P cultures. The biomass accumulation determined by carbon, indicated low N : P Aphanizomenon cultures did not have a N‐fixation growth trade‐off, in contrast to some other diazotrophs that maintain stoichiometric N homeostasis at the expense of growth. However, N‐fixing Aphanizomenon populations produced less particulate cylindrospermopsin and had undetectable dissolved cylindrospermopsin compared to non‐N‐fixing populations. The pattern of low to high cyanotoxin cell quotas across an N : P gradient in the diazotrophic cylindrospermopsin producer is similar to the cyanotoxin cell quota response in nondiazotrophic cyanobacteria. We suggest that diazotrophic cyanobacteria may be characterized into two broad functional groups, the N‐storage‐strategists and the growth‐strategists, which use N‐fixation differently and may determine patterns of bloom magnitude and toxin production in nature.